Understanding the mechanisms of hypoxia-induced tissue damage in fish: The role of GasderminEa/b in Larimichthys crocea - Lin Wang; Shuaiyu Chen; Yongyang Wang; Weini Zhang; Yinnan Mu; Yudong Jia; Changtao Guan; Meng Xue; Xinhua Chen (Water Biology and Security)
Hypoxia is one of the major environmental stressors, frequently resulting in serious yield losses for maricultured large yellow croaker (Larimichthys crocea). We know that pyroptosis contributes to tissue damage under hypoxic conditions. However, whether GSDMEs-mediated pyroptosis is involved in hypoxia-induced tissue damage in fish remains unclear. In the present study, two Lcgsdme genes, Lcgsdmea/b, were cloned and characterized from the large yellow croaker. Both genes contain a conserved N-terminal pore-forming domain, a C-terminal autoinhibitory domain, and a flexible hinge region. After hypoxia stress, the expression of Lcgsdmea/b transcripts and proteins in the liver were significantly higher than in unstressed fish. The proteins of LcGSDMEa/b could be cleaved under hypoxic conditions. Compared to LcGSDMEb, the expression of LcGSDMEa was higher in both mRNA and protein levels, thus exhibiting a stronger response during hypoxia stress. Furthermore, after 48 ​h of hypoxia stress, approximately 65% liver cells exhibited abnormalities, with pyroptosis being detected using a transmission electron microscope. TUNEL/LcGSDMEa double staining assay revealed a high expression of LcGSDMEa in the dead cells. We observed a significant up-regulation of pyroptosis pathway genes (asc, caspase-3) and pro-inflammatory cytokine genes (il-1β, il-18). After simultaneous knockdown of Lcgsdmea/b in vivo, the liver exhibited better health compared to the control group, with less cell swelling and vacuolation. Taken together, these findings demonstrate that hypoxia stress could activate LcGSDMEa/b and induce pyroptosis in the liver of large yellow croakers, thereby contributing to tissue damage. Our study improves the understanding of hypoxia-induced tissue damage in fish, and provides new clues for protecting fish against hypoxia-induced damage.